2011
DOI: 10.1007/s00429-011-0340-y
|View full text |Cite
|
Sign up to set email alerts
|

A deconvolution method to improve automated 3D-analysis of dendritic spines: application to a mouse model of Huntington’s disease

Abstract: Dendritic spines are postsynaptic structures the morphology of which correlates with the strength of synaptic efficacy. Measurements of spine density and spine morphology are achievable using recent imaging and bioinformatics tools. The three-dimensional automated analysis requires optimization of image acquisition and treatment. Here, we studied the critical steps for optimal confocal microscopy imaging of dendritic spines. We characterize the deconvolution process and show that it improves spine morphology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 71 publications
1
31
0
Order By: Relevance
“…The brains were removed and post-fixed for 1 h in the same fixative, and sections (150 μm) were cut with a vibratome. 21 Image stacks of MSN dendrites were acquired in the NAc shell using a 488 or 561-nm laser line for excitation of a Confocal Laser Scanning Microscope (SP5, Leica, Wetzlar, Germany). Image stacks were deconvoluted with Huygens 3.5 software (Scientific Volume Imaging).…”
Section: Diolistic Labeling and Dendritic Spine Analysismentioning
confidence: 99%
“…The brains were removed and post-fixed for 1 h in the same fixative, and sections (150 μm) were cut with a vibratome. 21 Image stacks of MSN dendrites were acquired in the NAc shell using a 488 or 561-nm laser line for excitation of a Confocal Laser Scanning Microscope (SP5, Leica, Wetzlar, Germany). Image stacks were deconvoluted with Huygens 3.5 software (Scientific Volume Imaging).…”
Section: Diolistic Labeling and Dendritic Spine Analysismentioning
confidence: 99%
“…growth and modulation of synaptic strength (41)(42)(43). Given that dysregulated neuronal morphology and altered synaptic strength occur in HD (44)(45)(46), the proteasome-mediated regulation of synaptic remodeling might be impaired in HD and is likely to play a critical role in HD pathogenesis. Collectively, these findings suggest that enhanced phosphorylation of Rpt6 at Ser 120 by PKA and CaMKII␣ provides a potential route to identify new therapeutic agents for treating HD.…”
Section: Figmentioning
confidence: 99%
“…1); thus, ROR␣ is present during the embryonic (E14, Hamilton et al, 1996) and early postnatal period and is then no longer synthesized starting at an age when CF synapse elimination is well underway or nearly complete (Kano and Hashimoto, 2009). Our morphological studies revealed dendritic changes and particularly a reversal of the CF somatodendritic translocation, suggesting functional changes in the CF/PC synapses.…”
Section: Rora Deletion In Pcs After the First Postnatal Week Triggersmentioning
confidence: 99%